Tracking the position of insole pressure sensors during walking and running - Chumanov, E. S.; Remy, C. D.; Thelen, D. G. (2007 Annual Meeting (NACOB) Ann-Arbor, 2007)
Pressure sensitive insoles have emerged as a powerful tool for assessing the pressure distribution on the sole of a foot. The pressures measured by the insole sensors can also be combined to determine a partial set of net ground reactions (COP-center of pressure, vGRF - vertical ground reaction force) (Barnett, et.al, 2000, Chesnin, et.al, 2000). Such information could conceivably be used within a least-squares inverse dynamics approach (Kuo, 1998) to estimate joint kinetics, thereby providing an alternative to fixed forceplates. However, using insoles for inverse dynamics analysis would require the global position of the insole sensors be tracked with high fidelity. This is a challenging requirement to achieve since the flexible insoles are embedded in a shoe which can undergo large motion and deformations. The objective of this study was to develop and evaluate the use of an array of motion capture markers affixed to a shoe to track insole sensor positions during walking and running. The accuracy of the approach was assessed by comparing the estimated position of the COP and the net vGRF with values measured using a fixed forceplate.